Exchange rate volatility in the eurozone - Oscar Bajo-Rubio; Burcu Berke; David G. McMillan (Economics: The Open-Access, Open-Assessment E-Journal, 2020)
The current economic crisis has witnessed a strong deceleration in the growth of international trade. This has been even greater in the cases of the European Union and the eurozone, where the rates of export growth have even reached negative figures. In this paper, the authors examine to which extent exchange rate volatility might account for the drop in the rate of growth of exports in the eurozone since the start of the crisis. To that end, they estimate export functions, augmented to include several measures of exchange rate volatility, for the four largest economies of the eurozone, i.e., France, Germany, Italy and Spain, for the period 1994:1-2014:4. In the empirical application, the authors make use of two alternative measures for exchange rate volatility, i.e., (i) the Standard deviation and (ii) the conditional variance from the GARCH methodology, of the change in the logarithm of the exchange rate, for both nominal and real exchange rates, and in the latter case computed using as deflators both Export prices and unit labour costs. The empirical results show no clear-cut evidence on the impact of exchange rate volatility on the exports of the countries analysed, suggesting that financial markets were developed enough so that exchange rate volatility does not hinder the evolution of exports.
Keywords: F31; F41; F45; 330; exchange rate volatility; exports; eurozone